CB1-mediated effects of delta-9-tetrahydrocannabinol (Δ9THC) on neuronal protein expressions in the hippocampus of male sprague dawley rats - Zakaria, Fatin Nadzirah (2013)
Neuroplasticity refers to the ability of the brain to respond as a result of a certain experience. Delta-9-tetrahydrocannabinol (Δ9THC), originally extracted from the female plant of Cannabis sativa is regarded as the most active psychotropic ingredient of cannabis. Cannabis sativa, the largest variety grows in both tropical and temperate climates. Δ9THC has been shown to affect sensory perception, cognition and memory, reward, appetite, motor coordination and attention. A recent review of references indicates that Δ9THC plays an important role in neuronal plasticity. In-vitro and in-vivo studies showed that administration of Δ9THC modulates several neuronal protein expressions involved in synaptic plasticity in hippocampal region. Previous studies have provided clues on how hippocampus plays an important role in memory process. However the molecular alteration and cellular mechanism leading to neuronal plasticity are not yet well understood. Therefore, the objectives of this study were to evaluate the effects of acute and chronic Δ9THC treatment on total ERK1 and ERK2 (p44 and p42 MAP kinase), p-ERK1 and p-ERK2 (p-p44 and p-p42 MAP kinase), CREB, p-CREB and c-fos protein levels in the rat hippocampus of brain by studying the CB1 receptor mechanism which includes the receptor agonist and antagonist. These proteins are thought to be involved in neuronal plasticity. This study was done in 3 experiments. Experiment 1 and 2, the rats were divided into 4 groups which were control group and three treated groups (0.5, 1.0 and 2.0 mg/kg Δ9THC) respectively. For acute treatment (experiment 1), the rats in control group received vehicle (2% ethanol + 0.9% NaCl) only while for treated group, the rats received 0.5, 1.0 and 2.0 mg/kg of Δ9THC which were administered every 48 hours for 7 days. For chronic treatment (experiment 2), Δ9THC (0.5, 1.0 and 2.0 mg/kg) were administered every 48 hours for 21 days. All drugs and vehicle were administered via intraperitoneal injection (i.p.). The volume of i.p. injection was 0.1 ml/100 g body weight. Based on the chronic study, 2.0 mg/kg Δ9THC which was the optimum dose were used in the combination treatment (experiment 3) to study the effect of chronic Δ9THC with pretreatment CB1 antagonist SR141716A (rimonabant). All drugs solution was prepared immediately prior to the experiment. The data were corrected on the basis of β-actin levels to normalize possible differences between each loading volume. The protein levels were presented as percentage changes compared with control group, designated as 100%. One-way ANOVA was performed followed by a post-hoc Tukey’s Multiple Comparison Test where applicable for inter-group comparison, with P<0.05 considered a significant difference. The result showed that acute Δ9THC treatment at all doses modulates the levels of ERK1, ERK2 (P<0.01),p-ERK1 (P<0.05; P<0.01), p-ERK2 (P<0.01), CREB and c-fos (P<0.05; P<0.01) proteins. However, only Δ9THC at 0.5 mg/kg modulates the level of p-CREB. These finding produce inconclusive result and future investigation needs to be explored. Meanwhile, for chronic treatment, administration of Δ9THC also modulates the levels of ERK1 (P<0.05; P<0.001), ERK2 (P<0.01), CREB, p-CREB (P<0.01) and c-fos (P<0.05) protein levels. There have a reduction in the level of p-ERK1 at Δ9THC 1.0 mg/kg. Generally, it supposed to be increased since it had been noticed that Δ9THC at 2.0 mg/kg showed significantly differences. The mechanism underlying these finding is remain unclear and considered as inconclusive result. The protein expression was also studied to determine whether the changes observed due to CB1 receptor activation using selective antagonist SR141716A. Based on the result obtained, pre-treatment with CB1 antagonist SR141716A failed to alter the Δ9THC induced effect on ERK1 and c-fos expressions. Interestingly, these effects can be reversed by SR141716A on ERK2, p-ERK1, p-ERK2 and p-CREB proteins. In conclusion, the present data suggest that synthesis of ERK1 and c-fos are not CB1 mediated effect but synthesis of ERK2 and activated of ERK as well as CREB by Δ9THC are through CB1 mediated effect pathway.